A stakeholder engagement method navigator webtool for clinical and translational science. Issue 1 (13th September 2021) - Kwan, Bethany M.; Ytell, Kate; Coors, Marilyn; DeCamp, Matthew; Morse, Brad; Ressalam, Julie; Reno, Jenna E.; Himber, Meleah; Maertens, Julie; Wearner, Robyn; Gordon, Kaylee; Wynia, Matthew K.
Abstract: Stakeholder engagement is increasingly expected by funders and valued by researchers in clinical and translational science, yet many researchers lack access to expert consultation or training in selecting appropriate stakeholder engagement methods. We describe the development of a novel Stakeholder Engagement Navigator webtool. We conducted an environmental scan and literature review, along with investigator interviews, surveys, and engagement expert facilitated group discussion. We formally reviewed and cataloged 29 distinct engagement methods. To develop the webtool, we used an iterative design process that followed Design Thinking phases: empathize, define, ideate, prototype, and test. As prioritized during user testing, the Stakeholder Engagement Navigator webtool both educates and guides investigators in selecting an engagement method based on key criteria. The V1.0 Navigator webtool filters methods first by purpose of engagement (noted by 62% of users as the highest priority criteria), then by budget, time per stakeholder interaction, and total interactions. The tool is available at DICEMethods.org. The Stakeholder Engagement Navigator webtool is a user-centered, interactive webtool suitable for use by researchers seeking guidance on appropriate stakeholder engagement methods for clinical and translational research projects.